Dividends and share repurchases from investor’s perspective - Usvajärvi, Niko (My University, 2025)
The purpose of this thesis is to examine whether dividends or share repurchases are a better option for the investor. More specifically, focusing on whether investors prefer one over the other and possible stock reactions to share repurchase announcements. During the past few decades, the dominant payout method has evolved greatly with repurchases exceeding tradi tional dividends. Understanding how these methods impact investor perception and interpreta tion of firms is crucial. The study aims to shed light on why payout decisions may impact stock prices despite the dividend irrelevance proposition. A review of empirical literature shows that share repurchase announcements frequently occur with positive abnormal stock returns. While a major segment of investors seem to prefer share repurchases, dividends remain important to many which suggests that a mix of both dividends and share repurchases seems to be the pref erence of investors.

Tämän tutkielman tavoitteena on selvittää ovatko osingot vai omien osakkeiden takaisinostot sijoittajalle parempi vaihtoehto. Tarkemmin ottaen tarkastellaan suosivatko sijoittajat jompaakumpaa menetelmää ja miten osakekurssit reagoivat omien osakkeiden takaisinostoilmoituksiin. Viime vuosikymmenenä pääoman jakotapa on kehittynyt valtavasti ja omien osakkeiden takaisinostot ovat ohittaneet perinteiset osingot. On tärkeää ymmärtää, miten nämä menetelmät vaikuttavat sijoittajien käsityksiin ja tulkintoihin yrityksistä. Tutkimuksen tavoitteena on selvittää, miksi voitonjakopäätökset voivat vaikuttaa osakekursseihin osinkojen merkitsemättömyysteoriasta huolimatta. Empiirinen kirjallisuus osoittaa, että osakkeiden takaisinostoja koskevat ilmoitukset johtavat usein positiivisiin epänormaaleihin tuottoihin. Vaikka suuri osa sijoittajista näyttää suosivan osakkeiden takaisinostoja, on osingonjako monelle edelleen tärkeä. Tämä viittaa siihen, että sijoittavat näyttävät suosivan sekä osinkojen että takaisinostojen yhdistelmää.
Keywords: dividends; shares; investors; repurchases; preferences; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|